Analysis of Strengthening Moral Values through Digital-Based Islamic Religious Education Learning - Tri Selo Cahyono; Robingun Suyud Elsyam; Muhtar sofwan Hidayat (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This article examines the strengthening of moral values through digital-based Islamic Religious Education (IRE) learning within the rapidly transforming landscape of contemporary education. The study aims to understand how digital platforms, learning media, and pedagogical designs contribute to the internalization of moral values among students. The topic is significant because digitalization not only creates new opportunities for value-oriented learning but also introduces risks that may weaken students’ moral awareness. Using a systematic literature review, this study analyzed eight primary research articles published within the last decade. No hypothesis was tested, as the study relied entirely on qualitative and conceptual analysis. The findings reveal a surprising paradox: digital learning can strengthen moral values when guided pedagogically, yet it can also diminish them when students interact with digital content without ethical supervision. The study contributes to the discipline by offering a conceptual model that positions digital ethics and moral habituation as key mediating variables in value internalization. The conclusion highlights the urgent need for ethical-oriented digital pedagogy and capacity building for teachers in designing value-integrated digital learning. These results underscore the importance of rethinking digital IRE not merely as a technological shift but as a moral-educational transformation.